Cannabinoid Receptor Activation Disrupts the Internal Structure of Hippocampal Sharp Wave-Ripple Complexes - Yi Sun; Hiroaki Norimoto; Xiao-Ping Pu; Norio Matsuki; Yuji Ikegaya (Elsevier, 2012)
Cannabinoid agonists impair hippocampus-dependent learning and memory. Using mouse hippocampal slice preparations, we examined the effect of anandamide, an endogenous cannabinoid, on sharp wave-ripple (SW-R) complexes, which are believed to mediate memory consolidation during slow-wave sleep or behavioral immobility. Anandamide reduced the frequency of SW-Rs recorded from the CA3 region, and this effect was abolished by AM251, a cannabinoid CB1-receptor antagonist. We further addressed the action of anandamide using a functional multineuron calcium imaging technique. Anandamide reduced the firing rate of hippocampal neurons as well as disrupted the temporal coordination of their firings during SW-R. Keywords:: hippocampus, local field potential, memory consolidation, endocannabinoid, type 1 cannabinoid (CB1) receptor